Limites estruturais do sistema de precedentes judiciais adotado no Brasil - Almeida, Michael Estevam de (Universidade Federal Rural do Semi-Árido, 2020)
This monograph refers to the binding precedent system established by the Code of Civil Procedure of 2015, which expanded the hypothesis of binding decisions, a standard instrument of jurisprudence initiated with the amendment to the Federal Constitution no . 45 (Binding Summary, Direct Action of Unconstitutionality and Declaratory Action of Constitutionality). With the aforementioned systematic, a new legal hermeneutic moment in the country was pointed out, bringing the current legal system, which is characteristically civil law, closer to the common law legal tradition, in which the binding of previous decisions has a historical and central role. Greater uniformity in the judgments rendered, which often present conflicting decisions on the same issue of law, is the main justification for this approximation of legal systems. With the change, the merely persuasive character of jurisprudence was abandoned in order to assume the normative role of precedents in resolving demands. However, it is necessary to investigate whether the system created is in line with constitutional principles. Therefore, the problem is whether the system of binding precedents, in the way it is structured, is constitutionally adjusted. The research is bibliographic in nature, the deductive method was used, based on the legal and doctrinal examination on the topic. As a result, it was inferred that there are structural limits, with regard to the insertion of precedents in the legal body, with inadequate insertion (legislative option). Furthermore, there were limits related to the overcoming of precedents regarding decisions of general repercussion and judgments of repetitive cases, due to the non-possibility of access by the courts to the Superior Courts. Limits were also observed regarding the application of the precedents, with the possibility of making decisions applied to subsequent cases in the wrong way or without paying attention to all the circumstances that may differentiate the cases, which, as a consequence, would offend the principle of isonomy. Thus, it is concluded that the system created is not in line with constitutional principles, because, as it was created, there may be a “plastering” of the Law, not consistent with the performance of the Judiciary in the current Democratic State of Law which, as is known, must regulate social relations, political and economic aspects of society
Keywords: Constituição; Processo civil; Sistemas jurídicos; Precedentes; Inconstitucionalidade; Constitution; Civil procedure; Legal systems; Precedents; Unconstitutionality; CIENCIAS SOCIAIS APLICADAS::DIREITO